Hubungan Program Radio “Genk Ladies” terhadap Pemenuhan Kebutuhan - Reni Renita; Nova Yuliati (UNISBA Press, 2022)
Abstract. Radio as a mass media that provides information, entertainment and education through transmission waves and is widespread. Over time, there have been many non-government or private radio stations in Indonesia accompanied by various radio segments. The growth of female radio in Indonesia provides many benefits for radio listeners with the female segmentation. One of the female radios in Bandung is B-Radio 95.6 FM Bandung which has a lot of broadcast programs such as “Genk Ladies” which provides information about entertainment news, gossip, and Indonesian and Korean songs. In preparing this report, quantitative research methods and correlational approaches were used to obtain data and information with a population of 9,286 people and 99 people as respondents. The data was collected by distributing questionnaires using random sampling technique. In this study using the theory of media exposure. Then, use the uses & gratifications proposed by Katz, Blumer, and Gurevitch. The purpose of this study was to determine the extent to which the radio broadcast of